Soluble receptor for advanced glycation end-products (sRAGE) and colorectal cancer risk: a case–control study nested within a European prospective cohort - Aglago, EK; Rinaldi, S; Freisling, H; Jiao, L; Hughes, DJ; Fedirko, V; Schalkwijk, CG; Weiderpass, E; Dahm, CC; Overvad, K; Eriksen, AK; Kyrø, C; et al. (American Association for Cancer Research, 2020)
Background: Overexpression of the receptor for advanced glycation end-product (RAGE) has been associated with chronic inflammation, which in turn has been associated with increased colorectal cancer risk. Soluble RAGE (sRAGE) competes with RAGE to bind its ligands, thus potentially preventing RAGE-induced inflammation.